Development of a health communication campaign to promote the Texas prescription monitoring program. Issue 3 (2nd July 2020) - Mackert, Michael; Pounders, Kathrynn; Brown, Laura E.; Kirtz, Susan; Wagner, Jessica Hughes; Ring, David; Hill, Lucas; Wilcox, Gary; Murthy, Dhiraj; Tierney, William; Innerarity, Sheri; McGlone, Matthew; et al.
Abstract: Given the role opioid overprescribing has played in the current overdose crisis, reducing the supply of prescription opioids available for misuse has gained widespread support. Prescription monitoring programs (PMPs) have been identified as a tool for achieving this goal, but little is known about how to promote PMP use to prescribers. This paper describes the process of developing a health communication campaign to support the adoption of the Texas PMP. After formative research, message development and concept testing, a range of campaign concepts and messages were tested and final recommendations determined. The messages and lessons learned have utility beyond Texas.